1959
DOI: 10.1677/joe.0.0180186
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Pseudopregnancy in the Mouse

Abstract: From 20 to 50 % of sexually mature female mice, grouped together in large cages but isolated from males since weaning, were found to be pseudopregnant as indicated by abeyance of oestrus, vaginal mucification, weight changes and mammary development. Such 'extra-coital' pseudopregnancies occurred independently of experimental handling in grouped females but were also observed, although much less frequently, in isolated mice subjected to daily examination.The duration of pseudopregnancy was found to be longer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 1 publication
(3 reference statements)
0
14
0
Order By: Relevance
“…This suggests that the latter situation supplies a stronger stimulus. When the test situation concerns females only (see Tables 2 and 3) there is no mutual interference with pregnancy, but mutual interference between females is well known to occur as regards the oestrous cycle (van der Lee & Boot, 1955, 1956Whitten, 1957b;Dewar, 1959) where the proximity of other females appears conducive to the formation of corpora lutea with the induction of pseudopregnancy. It seems probable that the absence of failed luteal function among the test groups containing only females is an expression of this reaction.…”
Section: The Femalesmentioning
confidence: 99%
“…This suggests that the latter situation supplies a stronger stimulus. When the test situation concerns females only (see Tables 2 and 3) there is no mutual interference with pregnancy, but mutual interference between females is well known to occur as regards the oestrous cycle (van der Lee & Boot, 1955, 1956Whitten, 1957b;Dewar, 1959) where the proximity of other females appears conducive to the formation of corpora lutea with the induction of pseudopregnancy. It seems probable that the absence of failed luteal function among the test groups containing only females is an expression of this reaction.…”
Section: The Femalesmentioning
confidence: 99%
“…This is indicated also in the reduction from the 8th day onwards of the variability of this parameter (as shown by the increasing reduc¬ tion in the standard deviation-see Table 3 and Text- fig. 2) ; in this strain of mice, the duration of activity of the CL of pseudopregnancy is very variable (Dewar, 1959 and Tables 1 and 2), the range extending from 9 to 36 days, and a considerable proportion of the animals having pseudopregnancies as long as, or longer than, the gestation period (27% of 193 pseudopregnancies examined lasted 19 days or over). The abolition of this variability in CL activity in pregnancy suggests that the luteotrophic influence of the pituitary which initiates such activity not only becomes redundant in later pregnancy but is suppressed (after about the 13th day).…”
Section: Influence Of Hysterectomy On the Oestrous Cyclementioning
confidence: 89%
“…Newton (1935) noted that the interval between uterine evacuation and oestrus in a few animals was somewhat longer when the operation was performed on the 12th as compared with the 18th day of preg¬ nancy, but no reinvestigation of this observation has since been made. Although the earlier work has clearly established the dependence of the CL on placental endocrine function, the degree of this dependence may be questioned in the light of more recent observations on the duration of pseudopregnancy which, in some mice, can be as long as the normal gestation period (Dewar, 1959). The rôle of the uterus itself in the control of the CL of pregnancy requires further investigation although the indications are (Dewar, 1957a;McLaren, 1970) that it plays no significant part.…”
Section: Introductionmentioning
confidence: 98%
“…The oestrous cycle of the mouse is influenced by environmental conditions (Merton, 1937; Van der Lee & Boot, 1955, 1956Dewar, 1959). Contact with intact, but not castrated, male mice shortens the oestrous cycle (Whitten, 1958;Bruce, 1965).…”
mentioning
confidence: 99%
“…The suppressive effect was abolished by ovariectomy, except that a small effect on the length of the cycle remained (Table 3). (Terenius, 1971 (Champlin, 1971), although Dewar (1959) has suggested that mounting behaviour is important, and Kimura (1971) …”
mentioning
confidence: 99%